2015
DOI: 10.3238/arztebl.2015.0577
|View full text |Cite
|
Sign up to set email alerts
|

The Treatment of Primary Breast Cancer in Older Women With Adjuvant Therapy

Abstract: The cause of these age-related differences is unclear. It cannot be determined from these data whether concomitant disease, the older patients' individual decisions, or other factors were responsible for their not receiving treatment as often as the younger patients did.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 37 publications
0
7
0
1
Order By: Relevance
“…At the same time, DFS was significantly shorter in the group of older women. Several retrospective studies investigating the use of adjuvant chemotherapy in elderly patients have reported different treatment rates in the range from 5 to 32 % (Vlastos et al 2001;Woodard et al 2003;Brunello et al 2005;Hawfield et al 2006;Peters et al 2015). However, these studies are not readily comparable due to differences in age distributions and patient characteristics.…”
Section: Discussionmentioning
confidence: 87%
“…At the same time, DFS was significantly shorter in the group of older women. Several retrospective studies investigating the use of adjuvant chemotherapy in elderly patients have reported different treatment rates in the range from 5 to 32 % (Vlastos et al 2001;Woodard et al 2003;Brunello et al 2005;Hawfield et al 2006;Peters et al 2015). However, these studies are not readily comparable due to differences in age distributions and patient characteristics.…”
Section: Discussionmentioning
confidence: 87%
“…P values of < 0.05 were considered to indicate statistical significance. Given the risk of α- error from many statistical analyses, we additionally adjusted Bonferroni's correction for the P values as reported [ 15 ]. P values of < 0.0042 were considered to indicate statistical significance after Bonferroni's correction, as 12 individual tests were performed (0.05/12).…”
Section: Methodsmentioning
confidence: 99%
“…Age affects the type of surgery. This is especially true for breast-conserving surgery, which is offered less often to older patients [32, 33]. Not only specialists but also patients opt for more aggressive interventions.…”
Section: Surgerymentioning
confidence: 99%
“…A positive axillary lymph node status results in an increased use of radiation [37, 47]. An advancing age and increased comorbidity have the opposite effect [33-35, 47-51]. It is estimated that only two thirds of patients aged 71—80 years, with an indication for RT, actually receive it [51].…”
Section: Radiation Therapymentioning
confidence: 99%